(untitled) (Journal of Health Sciences, 2017)
Introduction: We studied the chemical composition and antimicrobial, antioxidant, and antiproliferative activities of essential oils from flowers of Lavandula angustifolia grown in Southern Bosnia and Herzegovina. Methods: The chemical profile of essential oil was evaluated by means of gas chromatography-mass spectrometry. Antimicrobial activity was tested against six bacterial strains. The antioxidant activity by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) test and the antiproliferative activity against three human cancer cell lines, MCF-7, NCI-H460, and MOLT-4, were investigated using 3-(4,5-dimethylthiazol-2-Yl)-2,5-diphenyltetrazolium bromide tests. Results: In L. angustifolia essential oil, monoterpene alcohols were the most represented class of volatiles (51.8%), including linalool, lavandulol, and terpinen-4-ol, α-terpineol as the major components, followed by monoterpene esters (22.6%). The most important antibacterial activity of essential oil was expressed on Gram-negative strains. Investigated essential oil was able to reduce DPPH radicals into the neutral DPPH-H form (inhibitory concentration 50% [IC50] = 0.421 mg/ml), and this activity was dose dependent. The essential oil showed significant antiproliferative activity against three cancer cell lines, MOLT-4, MCF-7, and NCI-H460 cells, with IC50 values of 17, 94, and 97 µg/ml, respectively. The result of the antiproliferative assay indicates that MOLT-4 cell line was the most sensitive to investigated essential oil. Conclusion: The results revealed that L. angustifolia essential oil may be important growth inhibitor against the microbes studied. It also possesses significant antioxidant activity and demonstrated excellent antiproliferative activity against MOLT-4 cells.